Expert System For Failure Diagnosis Of Cvt 125/150 Led Motorcycle Using Website Based Forward Chaining Method - Ahmad Muflih; Cindy Taurusta; Ade Eviyanti (Procedia of Engineering and Life Science, 2022)
Abstract-Over time, many people who previously did not use automatic motorbikes turned to automatic motorbike users because the way they were used was very easy and different from other types of motorbikes. Behind the easy way of using it, there are many problems that arise in automatic motor components, especially on the CVT. Not everyone understands the problem with the CVT. Some users prefer to take their motorbikes to both official and non-official workshops. So the development of an expert system, is a computer science that works like an expert. Forward Chaining method, a forward search method that begins with a fact will later produce a conclusion. The results show that an expert system for diagnosing automatic motorcycle damage using the forward chaining method helps users anticipate damage so that there will be no greater and sustainable damage.